A deep insight into the preparation of ceramic bone scaffolds utilizing robocasting technique. Issue 5 (1st March 2022) - Monfared, Mahdieh Hajian; Nemati, Alireza; Loghman, Fatemeh; Ghasemian, Melina; Farzin, Ali; Beheshtizadeh, Nima; Azami, Mahmoud
Abstract: From long ago, orthopedists and physicians are trying to deal with bone diseases and disorders, while today, in the regenerative medicine field, bone scaffolds are being in attendance. Although there were common methods for fabricating bone scaffolds, such as foam casting and gas foaming, additive manufacturing (AM) techniques have been considered for producing bone scaffolds due to some appealing features such as creating a hierarchical structure, regular and controlled porosity, and designing of the complicated structures. AM techniques are divided into three categories, including extrusion-based, powder-based, and vat polymerization (light-based) techniques. Among the AM methods, the robocasting technique as an extrusion-based method is highly regarded for designing high-strength scaffolds for bone tissue regeneration owing to special features, for instance, a low-volume binder and the ability to print all types of ceramic materials as well as metals and polymers. This study discusses the robocasting method, as well as the essential parameters that are involved in 3D printing of the ideal scaffold with this method, such as the material, the structure of the robotic device, the printing parameters, the properties of the ideal paste or ink, the role of binder and its types in robocasting, and the rheological properties required in robocasting method. Also, future prospects and clinical applications of this technique were reviewed.